The Effect of Intense Exercise on Equine Serum Proteoglycan-4/Lubricin - Matheson, Austyn; Regmi, Suresh C.; Jay, Gregory D.; Schmidt, Tannin A.; Scott, W. Michael (Frontiers in Veterinary Science, 2020)
Objective: Local biological and biomechanical-stimuli modulate proteoglycan-4 secretion within synovial joints. For the horse, changes to proteoglycan-4 concentration and function are notable in acute joint injury and osteoarthritis. Proteoglycan-4 (also known as Lubricin) is present in the blood, however the effect of exercise on equine serum levels is unknown. The overall objective of this study was, therefore, to investigate the effect of intense exercise on serum proteoglycan-4 in thoroughbred horses. Methods: Samples of blood were taken from thoroughbreds (n = 12) during a chuckwagon racing event (Alberta, Canada). The chuckwagon race is a sprint racing event where teams of horses pull a combined 1,325 lbs (601 kg) of wagon and driver around a 5/8th mile (1 km) of dirt track, racing at full gallop to the finish. Blood samples were collected 30-min before the race start, and several timepoints post-race: 5-min, 90-min, 3-h, 12-h, and 23-h. Proteoglycan-4 concentrations in serum were quantified by enzyme-linked-immunosorbent-assay using recombinant-human proteoglycan-4 standards and anti-proteoglycan-4 mAb 9G3. The molecular weight of immunoreactive proteoglycan-4 in serum was assessed by western blot. Results: Proteoglyan-4 in serum demonstrated the expected high MW immunoreactivity to mAb 9G3, consistent with that of full length PRG4. Serum proteoglycan-4 decreased five-minutes post-race from baseline concentration (0.815 ± 0.175 to 0.466 ± 0.090 μg/mL, μ ± SEM, p < 0.01). Conclusions: The concentration of serum proteoglycan-4 in horses decreased significantly five min post-exercise. A potential explanation for this finding could be increased proteoglycan-4 clearance from the circulation. Further investigations could extend to complete the detailed characterization of proteoglycan-4 structure and its potential function within the blood as it relates to joint health and exercise.